A Structured Approach to the Improvement of a Partially Automated Process using Six Sigma Methodology within a Community Pharmacy - McKenzie, Ian (2013)
Following investment in automated technology within a community pharmacy there was found to be an increased demand on resource and reduction in key performance indicators. The case study details the application of the DMAIC methodology which resulted in improvements to the filling process. The outcome was a reduction of 40% in the time taken to fill per channel. The number of steps within the process was reduced from 19 to 16 and the distance travelled reduced from 16.25 meters to 7.10 meters.